Pengungkapan ESG dan Kinerja Keuangan bagi Nilai Perusahaan Dimoderasi oleh Ukuran Perusahaan - Khansa Hasna Nur Khairunnisa; Tantina Haryati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The value of a company or business entity can reflect the condition and achievement of the business entity's goals. There are many aspects that are considered capable of influencing company value, some of which are Environmental, Social, Governance (ESG), Return on Assets (ROA), Return on Equity (ROE), and company size. This study seeks to explain how these aspects interact to influence company value. The research method used is quantitative by utilizing the annual reports of energy sector companies listed on the IDX for 2018-2022. The sampling technique in this study was purposive sampling and a sample of 16 companies was obtained. The data in this study was analyzed using the Partial Least Square - Structural Equation Modeling (PLS-SEM) method using SmartPLS 3 software. The results of the study analysis prove that ESG and ROA disclosures are able to influence company value with a positive and significant influence, then ROE has not affected the value of a company. Apart from that, company size is unable to provide a moderating effect on the interaction between ESG disclosure, ROA or ROE with company value. However, even though the findings in this study show that there are aspects that have not been able to influence the value of a company, companies still have to pay attention to these aspects for the sustainability of their business in the future.